Analisis studi kelayakan bisnis pada UD Republik Meri dan kripik tempe Azizah Sanan ditinjau dari aspek hukum - Qodratullah, M. Qori’; Faiz, Mochamad Wildan; S, Nihayatu Aslamatis (Maliki Interdisciplinary Journal, 2024)
This research discusses a business feasibility study at UD Republik Meri and Kripik Tempe Azizah Sanan. The purpose of this research is to determine the feasibility of the business run by UD Republik Meri and Kripik Tempe Azizah Sanan. The choice of location for the business feasibility study at UD Republik Meri and Kripik Tempe Azizah Sanan was due to the researchers' findings regarding the phenomenon in this business and the research process which was easy to reach. The methods used in collecting data in this research were interviews, observation and documentation with business actors, employees and local residents or community leaders. The business feasibility study in this research is reviewed from six aspects, namely legal aspects, environmental aspects, market and marketing aspects, technical and technological aspects, management, organizational and HR aspects, and financial aspects. The results of this research indicate that the business carried out by UD Republik Meri and Kripik Tempe Azizah Sanan is feasible based on the assessment of these six aspects.